Leadership Characteristics of School Administrators under the Nongchok District Office, Bangkok Metropolitan Administration - พันนนท์ จิราวรรณ; ประเสริฐสิน อัจศรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to: 1) examine the leadership characteristics of school administrators; 2) compare the leadership characteristics of school administrators; and 3) explore guidelines for developing the leadership characteristics of school administrators. The sample group consisted of 252 participants, determined using the sample size table of Krejcie and Morgan (1970: 607–610). The sampling methods included stratified random sampling and simple random sampling. The research instruments were a five-point rating scale questionnaire, with an index of item-objective congruence (IOC) ranging from .80 to 1.00 and a reliability coefficient of .888, as well as a semi-structured interview form. The statistics used for data analysis were mean, standard deviation, t-test, F-test, and content analysis. The research findings revealed that: • The overall level of leadership characteristics of school administrators was at a high level. When considering each aspect, the aspect with the highest mean score was enthusiasm, which was at a high level, followed by honesty and integrity, also at a high level. The aspect with the lowest mean score was self-confidence. • The comparison of leadership characteristics of school administrators classified by gender and educational level showed no significant differences in both overall and individual aspects. However, differences in work experience resulted in statistically significant differences at the .01 level in the aspects of honesty and integrity and commitment to development and achievement. Other aspects showed no differences. • The guidelines for developing leadership characteristics of school administrators include: administrators should think rationally and carefully, adhere to moral principles and correctness, have self-confidence while being open to and accepting others’ opinions, possess emotional maturity to create a positive working atmosphere, demonstrate commitment and systematic work toward the success of educational institutions, and maintain enthusiasm as an important driving force for the organization.